The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0263178
|View full text |Cite
|
Sign up to set email alerts
|

Malaria treatment-seeking behaviour and its associated factors: A cross-sectional study in rural East Nusa Tenggara Province, Indonesia

Abstract: Introduction The World Health Organization recommends seeking medical treatment within 24 hours after transmission of malaria to reduce the risk of severe complications and its onwards spread. However, in some parts of Indonesia, including East Nusa Tenggara Province (ENTP), this adherence is not achieved for a range of reasons including delays in visiting health centres. This study aims to determine factors related to the poor understanding of appropriate malaria treatment-seeking behaviour (AMTSB) of rural a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…More than a half of these febrile cases were treated with antimalarial drugs obtained from a local chemist. This is similar to studies in in Indonesia [16], Ghana [5], India [50], Myanmar [53], and Bangladesh [2] where majority of febrile patients reportedly preferred self-medication over hospital-based treatment. In the current study, key predictors of self-treatment included knowledge of malaria symptoms, severity of symptoms, and age of febrile patients.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…More than a half of these febrile cases were treated with antimalarial drugs obtained from a local chemist. This is similar to studies in in Indonesia [16], Ghana [5], India [50], Myanmar [53], and Bangladesh [2] where majority of febrile patients reportedly preferred self-medication over hospital-based treatment. In the current study, key predictors of self-treatment included knowledge of malaria symptoms, severity of symptoms, and age of febrile patients.…”
Section: Resultssupporting
confidence: 87%
“…Access to healthcare facilities, ability to pay hospital bills, severity of symptoms, and age of fever patients were factors that predicted treatment-seeking at healthcare facilities. The ease of access to healthcare facilities has been reported in previous studies to encourage treatment-seeking at healthcare facilities [16,25,37,60]. Easily accessible health facilities may not require transportation or may require only a small amount of money; as a result, the majority of people find it easy to access them.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results again contrast with the results of a recent study in Indonesia showing that 84.3% of communities seek care at modern health facilities (of which public: 82.4% and private: 1.9%), 7.9% at traditional healers, 4.3% at selfmedication and 3.4% at informal vendors in kiosks. 4 Thus, the study shows that a high proportion of households sought treatment for malaria outside health facilities. This result is in contradiction with studies conducted in India, Ghana, but they are consistent with findings from Saudi Arabia and Zambia, which indicate that a high proportion of the community seeks treatment at health facilities.…”
Section: Discussionmentioning
confidence: 84%
“…An analysis of the global malaria treatment database showed that treatment uptake rates differ both within and between regions. 4 Early treatment uptake plays an important role in the effective management of malaria. For this reason, WHO recommends that malaria treatment should be provided within 24 hours of the onset of malaria symptoms to prevent the progression of infection.…”
mentioning
confidence: 99%